2021
DOI: 10.23887/ijerr.v4i1.30443
|View full text |Cite
|
Sign up to set email alerts
|

Designing Educational Board Games For Children On Snake Handling Using Competitive Mechanisms

Abstract: Education with material and only listening to explanations make some people bored so that the information they want to convey is not well received. In addition, there is a lack of media that can educate snake handling and facilitate children in learning in a fun way and can be played outside of study hours. This study aims to analyze an educational board game for snake handling using competitive mechanisms in children. This research uses a descriptive method. The techniques used in collecting data are intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…After analyzing the results of interviews and previous theories, the author concludes that the use of Lazarus educational games as a learning medium can increase the motivation, interest, ability, and personality of students. The students show enthusiastic behavior and enjoy learning with the game, and show good skills and personalities when using the educational game Lazarus (Oktaviane et al, 2021;Supeni et al, 2019). Therefore, the educational game Lazarus is considered as one of the external factors that affect the learning outcomes of students, including in the availability of learning facilities.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing the results of interviews and previous theories, the author concludes that the use of Lazarus educational games as a learning medium can increase the motivation, interest, ability, and personality of students. The students show enthusiastic behavior and enjoy learning with the game, and show good skills and personalities when using the educational game Lazarus (Oktaviane et al, 2021;Supeni et al, 2019). Therefore, the educational game Lazarus is considered as one of the external factors that affect the learning outcomes of students, including in the availability of learning facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that some children are familiar with board games and interested in playing them as learning media. In previous research, board games can be used as an educational medium for elementary school children to properly distribute information about handling snakes (Oktaviane et al, 2021). In another study, board games can be an effective and interesting learning medium for junior high school teenagers to introduce various mobile phones at school or home.…”
Section: Introductionmentioning
confidence: 99%